2016
DOI: 10.1016/j.phrs.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological postconditioning against myocardial infarction with a slow-releasing hydrogen sulfide donor, GYY4137

Abstract: 36Exogenous hydrogen sulfide (H 2 S) protects against myocardial ischemia/reperfusion 37 injury but the mechanism of action is unclear. The present study investigated the 38 effect of GYY4137, a slow-releasing H 2 S donor, on myocardial infarction given 39 specifically at reperfusion and the signalling pathway involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 57 publications
1
49
1
Order By: Relevance
“…It is noteworthy that the optimum cardioprotective doses of GYY4137 and AP39 used were 26.6 and 0.25 μmol·kg −1 respectively. Very recently, we reported that 26.6 μmol·kg −1 GYY4137 was not cardioprotective in an in vivo rat model of ischaemia/reperfusion injury with the optimum cardioprotective dose being 10‐fold higher (Karwi et al ., ). Similarly, in the present study, we demonstrated that AP39 exerts an infarct‐sparing effect with an optimum cardioprotective dose of 1 μmol·kg −1 , fourfold higher than the effective dose in mouse reported by Chatzianastasiou et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is noteworthy that the optimum cardioprotective doses of GYY4137 and AP39 used were 26.6 and 0.25 μmol·kg −1 respectively. Very recently, we reported that 26.6 μmol·kg −1 GYY4137 was not cardioprotective in an in vivo rat model of ischaemia/reperfusion injury with the optimum cardioprotective dose being 10‐fold higher (Karwi et al ., ). Similarly, in the present study, we demonstrated that AP39 exerts an infarct‐sparing effect with an optimum cardioprotective dose of 1 μmol·kg −1 , fourfold higher than the effective dose in mouse reported by Chatzianastasiou et al .…”
Section: Discussionmentioning
confidence: 97%
“…Myocardial infarction was induced as previously reported (Karwi et al ., ). Briefly, rats were anaesthetized using thiobutabarbital (Inactin® 200 mg·kg −1 , i.p), and anaesthesia was maintained throughout the procedure by supplemental dosing (75 mg kg −1 , i.v.)…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Myocardial biopsies were collected at the end of perfusion for biochemical characterization, as previously described. [27][28][29] Briefly, protein samples (30 μg/well) were loaded onto 10% SDS-PAGE to be separated based on molecular weight, and were then transferred onto a nitrocellulose membrane using a wet-transfer method. The membrane was incubated with one of the following primary antibodies…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…It was unknown whether ROS played important roles on HK2 dimerization. To determine the role of ROS, GYY4137, a reductant reducing the cellular ROS, was employed. When cells were pretreated with GYY4137, then treated by GEM, the HK2 dimer was reduced compared with only GEM treatment in SW1990 cells (Figure H).…”
Section: Resultsmentioning
confidence: 99%